The Educational Inspection of Galicia: roads and future trails - Pérez Morán, Federico (Avances en Supervisión Educativa, 2009)
As is well known, the social sciences are concerned with organizing and interpreting the knowledge resulting from the reflection of societies on themselves. As an integral part of society and members of a collective, analyzing the past will help us understand the present and project the future. Following that pattern, we will review the brief history of the Galician Education Inspectorate to later analyze its current situation and make some proposals that may contribute to its improvement.